Pemeliharaan Allah dalam Konteks Bencana Alam (KENOSIS: Jurnal Kajian Teologi, 2024)
Natural disasters are unexpected events. Nobody knows when and how it will happen; indeed, nobody wants to experience a natural disaster. However, Natural disasters raise questions about the presence of God. The research is qualitative and uses a literature study approach. The purpose of this study is to explain the role of God in the survival of humans when facing natural disasters. The findings in this study are divided into three parts. First, Christianity acknowledges that natural disasters are part of God's work in human life. Second, God is always present and shows his care in human life. Third, the church is a manifestation of God's care in the context of natural disasters. Natural disasters will make us aware of our great responsibility as humans, which is evidenced by God's mandate to protect the universe. So, from natural disasters, believers can see God's care for his people.
Keywords: disaster; God's maintenance; church; nature